Financial Fitness: A Guide to Boosting Your Money Management Skills - Hendy Budianto; Andre Prasetya Willim; Alvin Lesmana (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study investigates the relationships between financial literacy, budgeting practices, financial behavior, and money management skills among customers of Bank Mandiri Pontianak Diponegoro. Using a quantitative research design with a sample of 90 customers selected via random sampling, data was collected using structured questionnaires. The analysis employed Smart PLS (Partial Least Squares Structural Equation Modeling) to examine direct and indirect effects. The findings reveal significant direct effects, where higher levels of financial literacy and effective budgeting practices are associated with improved financial behavior and enhanced money management skills. Indirect effects further underscore the role of financial behavior as a mediator between financial literacy/budgeting practices and money management skills. These results highlight the importance of promoting financial education and supporting disciplined budgeting practices to foster better financial behaviors and enhance overall financial well-being among bank customers.